PENGARUH KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL DENGAN VARIABEL MODERASI STRATEGI BISNIS, PERCEIVED ENVIRONMENTAL UNCERTAINTY (PEU), KETIDAKPASTIAN TUGAS DAN DESENTRALISASI - Lina Wiryana; Yvonne Augustine (Jurnal Magister Akuntansi Trisakti, 2014)
This study aimed to determine the effect of the characteristics of Information management accounting system on managerial performance with business strategy, Perceived Environmental Uncertainty (PEU), task uncertainty and decentralization as a moderating variable. Object of this study is the middle and top level managers of manufacturing companies in the Cikarang industrial area. The samples used in this study were 198. Data were analyzed using Multiple Regression Analysi.The results of the analysis stated, there is a significant positive effect between the characteristics of Information management accounting system on managerial performance. There is a significant positive effect in the interaction characteristics of Information management accounting system with business strategy, Perceived Environmental Uncertainty (PEU), task uncertainty on managerial performance,  there is no effect in the interaction characteristics of Information management accounting system with decentralization on managerial performance, also there is effect on simultant ways  between business strategy, Perceived Environmental Uncertainty (PEU), task uncertainty and decentralization in the interaction characteristics of Information management and on managerial performance.